ASUPAN ENERGI DAN ZAT GIZI SERTA ANTROPOMETRI BALITA STUNTING PADA SUPLEMENTASI ZINC PASCA VITAMIN A DOSIS TINGGI - Hendrayati; Nursalim; Satriyani Martha (Media Gizi Pangan, 2023)
The prevalence of stunted toddlers in Indonesia has changed from 35.6% in 2010 to 37.6% in 2013 and in 2018 it decreased to 27.7%. Even though there has been a decline in this figure, it is still a problem that must be resolved considering that the government program determines the prevalence of stunting at 14% in 2024. This study aims to determine the effect of zinc supplements on stunted toddlers after giving high doses of vitamin A on energy and nutrient intake, as well as anthropometry. Pre Test Post Test Group Design research design, the research was carried out for one month, namely giving zinc supplementation of 10 mg/day, to stunted children aged 2-4 years after giving high doses of Vitamin A. The sample was 45 people. The indicators measured are energy intake, macronutrient intake as anthropometry. The results of the study showed that giving zinc supplementation after giving high doses of vitamin A to stunted toddlers was not effective in terms of energy and macronutrient intake as well as anthropometry. Further research was carried out by looking at changes in biochemical levels such as levels of zinc, albumin, total protein and hemoglobin